2019
DOI: 10.1111/jar.12590
|View full text |Cite
|
Sign up to set email alerts
|

Impact of multiple co‐occurring emotional and behavioural conditions on children with autism and their families

Abstract: Background Comorbid conditions are very common in children and adults with autism spectrum disorder (ASD) and can affect school performance, adaptive skills and peer relationships. Comorbid conditions place strain on the family as well as the individual with ASD. This project aimed to determine the affect of comorbid conditions over and above child and family characteristics. Methods The present authors examined 3,055 cases of children with ASD who had varying numbers of comorbid conditions (i.e., ADHD, depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 62 publications
(76 reference statements)
0
13
0
Order By: Relevance
“…ID was defined by an IQ score below 70 in all studies. Prevalence of ID in ASD children ranged from 0.00% in children aged 3–4y ( 35 ) to 91.70% in female ASD aged 0-18y ( Figure 9 and Supplementary Material 6 ) ( 49 ). Prevalence of ID in Dovgan and Mazurek ( 49 ) was estimated based on telephone surveys aimed at parents of children with ASD and asked the following question: ‘have “a doctor or other health care provider ever told [him/her] that [the child] had” other specific co-occurring conditions?’.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ID was defined by an IQ score below 70 in all studies. Prevalence of ID in ASD children ranged from 0.00% in children aged 3–4y ( 35 ) to 91.70% in female ASD aged 0-18y ( Figure 9 and Supplementary Material 6 ) ( 49 ). Prevalence of ID in Dovgan and Mazurek ( 49 ) was estimated based on telephone surveys aimed at parents of children with ASD and asked the following question: ‘have “a doctor or other health care provider ever told [him/her] that [the child] had” other specific co-occurring conditions?’.…”
Section: Resultsmentioning
confidence: 99%
“…Prevalence of ID in ASD children ranged from 0.00% in children aged 3–4y ( 35 ) to 91.70% in female ASD aged 0-18y ( Figure 9 and Supplementary Material 6 ) ( 49 ). Prevalence of ID in Dovgan and Mazurek ( 49 ) was estimated based on telephone surveys aimed at parents of children with ASD and asked the following question: ‘have “a doctor or other health care provider ever told [him/her] that [the child] had” other specific co-occurring conditions?’. The study population was stratified by the number of co-morbidities, and the prevalence of 91.7% corresponded to the subpopulation of children who had ASD associated with three co-morbidities.…”
Section: Resultsmentioning
confidence: 99%
“…However, relatively little attention in the subgrouping literature has been given to co-occurring psychiatric symptoms, which have been recognized as an area of importance (Lombardo et al, 2019). The few studies that have considered co-occurring psychiatric symptoms when subgrouping samples of autistic children are limited in that they either focused on older, school-aged children (≥ 15 years) and aggregated all psychiatric symptoms into a single large category (Doshi-Velez et al, 2014) or focused on younger, preschool-aged children and kept psychiatric symptoms separated, even though multiple, co-occurring conditions are more common in older children (Wiggins et al, 2017;Dovgan & Mazurek, 2019;Nordahl et al, 2020). Additionally, all these studies included other child-level indicator variables (e.g., adaptive functioning, cognitive development) in their models along with psychiatric symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Co-occurring social-emotional and behavioural problems are common in autistic children (Dovgan & Mazurek, 2019; Totsika et al, 2011). In one group of school-aged autistic children (Mage = 10.91 years, standard deviation (SD) = 3.34), Hoffmann et al (2016) found clinically significant internalising and externalising behaviours in 70.8% and 41.5% of children, respectively.…”
mentioning
confidence: 99%